A case study approach to the learning effects of self-assessment in translation learning: evidence and mechanism - Wang, Tiantian; Zeng, Gang (Frontiers in Psychology, 2026)
While self-assessment has been widely studied, its cognitive-psychological mechanisms–particularly in translation learning–remain underexplored, especially within China’s higher education context. This study addresses this gap by investigating how learners generate feedback through scaffolded comparisons during self-assessment, a process central to metacognition and self-regulated learning. An English-major undergraduate with documented advanced translation competence and feedback literacy, established through 2 years of classroom observation, was purposefully selected for this case study, which tracked her interactions with multiple scaffoldings across iterative self-assessment cycles. Thematic analysis of interviews, combined with fine-grained analysis of translation products and scaffolding use, reveals that learners engage in dynamic comparisons between their outputs and available inputs, triggering learning effects. Crucially, the interactionist perspective frames these comparisons as psychologically meaningful interactions between learner beliefs and external supports, elucidating the cognitive mechanism behind self-assessment efficacy. By bridging cognitive science (metacognitive processes) and educational psychology (learner autonomy), this research advances process-oriented assessment models while hopes to contribute to mental well-being through its implications for reducing academic anxiety. More broadly, the findings speak to the potential of psychology-informed strategies in translation education to support the integrated development of professional competence and lifelong learning skills.